1989
DOI: 10.1152/ajpregu.1989.256.3.r646
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a physiological role for CCK in the regulation of food intake in mice

Abstract: The effects of L-364,718, a cholecystokinin receptor antagonist, on cholecystokinin octapeptide-induced inhibition of food, and its effect on food intake when given alone, were studied in mice using several different feeding paradigms. In all studies, L-364,718 (100 micrograms/kg, 1.0 mg/kg) reversed the ability of cholecystokinin octapeptide to decrease food intake. L-364,718 enhanced food consumption compared with controls in nonfasted mice (100 microgram/kg) and in prefed mice (50, 100, 250 micrograms/kg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
33
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 0 publications
6
33
1
Order By: Relevance
“…injection of devazepide whereas L-365,260 had no effect. The reversal by the CCK-A receptor antagonist was observed under conditions that did not influence basal food intake as reported previously (18,32). It is also unlikely to represent the anxiolytic-like effect of devazepide because L-365,260, which has established anxiolytic-like properties in mice (43,44), did not influence the food-suppressing effect of leptin-CCK.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…injection of devazepide whereas L-365,260 had no effect. The reversal by the CCK-A receptor antagonist was observed under conditions that did not influence basal food intake as reported previously (18,32). It is also unlikely to represent the anxiolytic-like effect of devazepide because L-365,260, which has established anxiolytic-like properties in mice (43,44), did not influence the food-suppressing effect of leptin-CCK.…”
Section: Discussionsupporting
confidence: 77%
“…Such a response is unlikely to reflect the anorectic effect of CCK. The peptide was injected at a dose of 3.5 g͞kg, subthreshold to induce a significant decrease in hourly food intake in lean mice, as reported previously (18,19,32). These data provide clear evidence for a synergistic interaction between leptin and CCK leading to short-term reduction in food intake upon a single peripheral injection in lean mice.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Animal studies have shown that CCK antagonists can increase food intake [80]. It would seem worthwhile to examine the effects of CCK antagonists in persons with the anorexia of aging.…”
Section: Cholecystokinin Antagonistsmentioning
confidence: 99%